Setting up and Running a Sharing Service: an Organisational Perspective - Luckner, Naemi; Fitzpatrick, Geraldine; Werner, Katharina; Subasi, Özge (Interaction design & architecture(s), 2015)
Enabled by web and mobile technologies, there has been an explosion of interest in the sharing economy and peer-to-peer exchange, with much high profile attention given to monetised exchanges such as in AirBnB and Uber. However there are also many other sharing initiatives, such as time banking, that focus on smaller, more local communities and do not involve monetisation of exchanges. While there is a growing body of literature elaborating participation and motivation in sharing services as well as analysing organisers’ roles, little is discussed about the work involved in the day-to-day organisation and management of such services. In this paper we report on an interview study with ten participants discussing five different sharing systems from three different countries. A qualitative thematic analysis of the data points to significant on-going effort reported by all to establish, maintain and grow a service, not only focussing on its practical aspects but also on growing a community and building trust. How they engaged in this practical work though was not so much shaped by the service model (time banking, LETS and so on) but on a complex relationship between their funding model, the service goal and whether it was a top-down or bottom-up initiative. These findings have implications for the design of technical platforms to support services, not just in elaborating a range of possible tasks to be supported but also in where and how it needs to be tailorable to certain needs, how adaptive it is to different service models and how it facilitates monitoring and reporting duties for organisers.